Perlindungan Hukum Bagi Konsumen Atas Produk Makanan Yang tidak Memenuhi Standar Mutu - Belassa, Saputra; Pesulima, Theresia Louize; Sopamena, Ronald Fadly (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2023)
Consumer protection is important considering the ever-increasing speed of science and technology. This research aims to examine how legal protection is for consumers for food products that do not meet quality standards and what legal measures can be taken by consumers who experience losses. The type of research used in this writing is normative legal research. By using a statutory approach and a concept approach. Analysis of legal materials uses qualitative methods, namely studies related to legal norms contained in statutory regulations and legal norms that exist in society. The qualitative analysis method is carried out by analyzing legal materials based on concepts, theories, laws and regulations, expert opinions and the author's own views that are relevant to the problem under study, then interpretation is carried out to conclude from this research question. The results of this research conclude that the form of legal protection for consumers in consuming food products based on the UUPK aims to protect consumers and monitor negligent actions on the part of business actors in managing food products, as an effort to empower business actors to be able to maintain the quality of their products, without intending to kill the businesses of business actors. the. The existence of the UUPK provides encouragement for business actors to become smart entrepreneurs and aware of the law in providing quality products. There are two legal remedies that Siwalima Ambon High School students can take as consumers for the losses experienced, namely by litigation legal remedies or legal remedies carried out in court through lawsuits for violations of the business actor and non-litigation legal remedies or legal remedies outside the court which can be resolved by Consumer Dispute Resolution Agency (BPSK) through mediation, arbitration and consolidation forums as regulated in Article 45 paragraphs 1 and 2 UUPK.